PROTECTIVE EFFECT OF SOYBEAN OIL ON MICE LUNG TISSUE INJURY AND ALVEOLAR HEMORRHAGE INDUCED BY BISPHENOL A - Shaukat, Sadia; Kundi, Hina; Ullah, Qazi Waheed; Waheed, Nazish; Deeba, Farah; Iftikhar, Shazia (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate histomorphological effects of Soybean oil supplementation on lung tissue injury and alveolar hemorrhage induced by Bisphenol A (BPA).Study Design: Laboratory-based experimental study.Place and Duration of Study: Anatomy department, Army Medical College, Rawalpindi and National Institute of Health, Islamabad, from Nov 2015 to Nov 2016.Methodology: Forty (40) healthy BALB/c mice of 9-11 weeks of age, weighing between 30-37gm were housed in a controlled environment at National Institute of Health. Group 1 (10) was control group. Group 2 (10) was given a daily dose of 50 milligram/kilogram body weight of Bisphenol A and group 3 (10) was given a daily dose of 500 milligram of Soybean oil and group 4 (10) was concurrently given Bisphenol A and Soybean oil with daily doses of 50 milligram/kilogram body weight and 500 milligrams. After a period of 8 weeks, animals were dissected 24 hours after receiving the last dosage. Lung wet weight, animal weight and relative body tissue weight index (RTBWI) were calculated. Tissue processing & staining was done. Alveolar hemorrhage was histomorphologically and statistically analysed using SPSS-21.Results: On microscopic examination, alveolar hemorrhage (AH) was observed in 10 (100%) group 2 specimens with increase in RTBWI and whereas only 5 (50%) of group 4 specimens had alveolar hemorrhage with slight improvement in relative body tissue weight index (RTBWI).Conclusion: Bisphenol A (BPA) induced lung injury as evident by intraalveolar hemorrhage, blood vessel congestion and increased RTBWI ratio were ameliorated by concomitant administration of Soybean oil.